2009
DOI: 10.1681/asn.2008050542
|View full text |Cite
|
Sign up to set email alerts
|

Renal and Brain Isoforms of WNK3 Have Opposite Effects on NCCT Expression

Abstract: Mutations in the WNK kinases WNK1 and WNK4 cause a rare familial form of hypertension (Gordon syndrome) by increasing expression of the thiazide-sensitive co-transporter NCCT in the kidney. Regulation of NCCT expression involves a scaffold of proteins composed of several kinases, including the third member of the WNK kinase family, WNK3. This protein, expressed in several tissues including kidney and brain, displays splice variation around exons 18 and 22. We expressed these proteins in Xenopus oocytes and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 25 publications
2
61
1
Order By: Relevance
“…There is no clear explanation for the discrepancies between our observations with WNK3-18b or WNK318bϩ22 and NCC and those of Glover et al (7). WNKs are complex kinases that are still poorly understood, but it seems that minimal disruption of their primary structures can prevent or switch their mode of action toward a particular target (13,23,29,32).…”
Section: C604contrasting
confidence: 99%
See 1 more Smart Citation
“…There is no clear explanation for the discrepancies between our observations with WNK3-18b or WNK318bϩ22 and NCC and those of Glover et al (7). WNKs are complex kinases that are still poorly understood, but it seems that minimal disruption of their primary structures can prevent or switch their mode of action toward a particular target (13,23,29,32).…”
Section: C604contrasting
confidence: 99%
“…The activation of NCC by WNK3-18a has been corroborated by other groups (7,32). In the present study, we tested the effects of all potential WNK3 variants on the activity of these cotransporters.…”
Section: Effects Of Wnk3 Variants On the Sodium-coupled Chloride Cotrsupporting
confidence: 60%
“…WNK3 is expressed in the brain and the kidneys as differently spliced variants due to the presence or absence of exons 18a or 18b, as well as of exon 22. One study showed that while the renal WNK3 isoforms activate NCC, the brain isoforms actually inhibit the cotransporter (24). However, another study reported that all WNK3 variants displayed the same effect on all members of the SLC12 family, including NCC (13).…”
Section: Wnk3 Is a Powerful Activator Of Nccmentioning
confidence: 99%
“…The phosphorylation of NCC is mediated by SPAK [79]; several WNKs interact with SPAK and therefore indirectly control the phoshorylation-step of NCC. Interactions between SPAK and WNK1 [79], WNK3 [34], and WNK4 [102] have been reported. However, the brain but not the kidney isoform of WNK3 can activate NCC and does so through a SPAKindependent mechanism [34].…”
Section: Kinasesmentioning
confidence: 99%
“…Interactions between SPAK and WNK1 [79], WNK3 [34], and WNK4 [102] have been reported. However, the brain but not the kidney isoform of WNK3 can activate NCC and does so through a SPAKindependent mechanism [34]. Two isoforms of SPAK have been identified, including full-length SPAK (FL-SPAK) and kidney-specific SPAK (KS-SPAK or SPAK2), of which the latter isoform has low expression levels in the DCT [73].…”
Section: Kinasesmentioning
confidence: 99%